PERANCANGAN ALAT PENDETEKSI PENEBANG LIAR MENGGUNAKAN SENSOR SUARA BERBASIS IoT-RASPBERRY PI - Surya Angga Pranata, I Putu Gede; Suartika, I Made; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2021)
Protected forest areas have the main function of protecting life support systems. The protected forest area of ??Ekasari Jembrana Bali has an area of ??1.603 hectares. In the Ekasari protected forest there are many illegal logging actions. In 2020 there were two cases of wood theft. The types of wood stolen were reed and rosewood. In addition to these two cases, in 2018 to 2019 there were more than 10 cases of illegal logging that occurred, it is necessary to have a tool that is able to detect the occurrence of illegal logging in protected forests. The working system of this tool uses a Pi NoIR camera module to take pictures and a sound sensor FC-04 to detect the sound of a chainsaw with a value of 55 dB. This tool uses a Raspberry Pi microcontroller which functions to receive and process data, so that it is able to display warnings on websites and telegram applications. This tool has a detection range of 1,1304 hectares, so 1.418 tools are needed in the entire protected forest area of ??Ekasari Jembrana Bali.